Sheet-like cleaning product imparting antifouling and / or antibacterial properties to object surface
By using a liquid combination of water-soluble polymers, antibacterial and antimold agents, and electrolytes in wet cleaning products, the problem that cleaning products in the prior art are difficult to maintain resistance to adhesion, antibacterial and mildew resistance under water contact, and innovation in maintaining cleaning effects under water or rainwater contact is achieved.
Patent Information
- Application Number
- JP2023158383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing wet cleaning products have difficulty maintaining adhesion, antibacterial and mildew resistance under water contact, especially on items that are frequently exposed to water or rainwater.
The liquid combinations containing water-soluble polymers, antibacterial and anti-mold agents with hydroxy acids or salts thereof, and electrolytes are used to maintain their effect in water by forming a stable complex.
It achieves the effect of keeping the surface free from dirt under water or rainwater contact, easy to rinse, antibacterial and anti-mold, and is suitable for the surface of various materials, including aqueous and aqueous materials.
Smart Images

Figure 2025049891000001 
Figure 2025049891000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a sheet-like cleaning article impregnated with a liquid composition for use in homes and the like. [Background technology]
[0002] Stains occur in various places in a home, and various cleaning agents are available to remove these stains.
[0003] In particular, window panes, screens, blinds, vehicle covers, tents, and eaves tents are prone to becoming soiled because they face the outdoors, and when it rains, dirt from the rainwater and soil splashed up by the rainwater adheres to them. When washing one's body, oily dirt, soap, shampoo, etc. that is washed off splashes onto the shower curtain of a unit bath, and bacteria grow there, causing pink slime and black mold stains. The same is true for toilets and around kitchen sinks. In this way, places where water (rainwater) is present are prone to becoming soiled and are troublesome places. This naturally requires frequent cleaning, and they are places that require a lot of effort to keep clean.
[0004] For example, wet-type sheet products that are impregnated with a certain amount of cleaning liquid are suitable for easily cleaning glass, bathroom and toilet floors, walls, doors, around kitchen sinks, etc. Wet-type sheet products are also suitable for easily cleaning cloth-like products (woven and non-woven) such as blinds, screen doors, vehicle covers, tents, shower curtains, etc. Wet-type sheet products that wipe these areas to remove dirt have already been proposed. In addition, products that claim to have effects such as sterilization and virus inactivation, and anti-soiling, anti-bacterial, and anti-fungal properties for the surface to be wiped have been proposed.
[0005] For example, Japanese Patent Application Laid-Open No. 2006-307389 proposes a toilet cleaning sheet impregnated with a cleaning liquid containing an amphoteric polymeric compound, a cationic polymeric compound, a nonionic polymer, or the like, which has an antifouling function.
[0006] Japanese Patent Application Laid-Open No. 2011-30793 describes a cleaning wet sheet in which a water-disintegratable sheet is impregnated with an aqueous liquid containing silicone that forms an anti-fouling coating on the toilet bowl.
[0007] JP 2021-172715 A describes a sheet-shaped cleaning product in which water-disintegrable paper is impregnated with an anti-soiling cleaning solution containing a ternary amphoteric polymer.
[0008] JP 2022-118980 A describes a cleaning sheet for disinfection, virus inactivation, and stain prevention, which is impregnated with an aqueous disinfectant containing a quaternary ammonium salt and a cationic polymer.
[0009] Wet wipe products that impart antibacterial properties after cleaning have also been proposed.
[0010] Japanese Patent Application Laid-Open No. 2018-90564, Japanese Patent Application Laid-Open No. 2019-112342, Japanese Patent Application Laid-Open No. 2022-49134, etc. disclose wet wipes that are impregnated with an aqueous liquid containing a quaternary ammonium salt or the like to provide disinfecting properties, virus inactivation, and even antibacterial and antifungal properties to the wiping surface.
[0011] However, even if antifouling ingredients or antibacterial / antifungal ingredients are left on the wiped object, these ingredients easily wash off in places where water splashes on them, making it difficult to maintain their effectiveness for a long time. In particular, it is difficult to fix antifouling ingredients, antibacterial / antifungal ingredients, etc. so that they do not wash away with water due to electrostatic interactions on objects made of low-polarity materials such as plastic. Furthermore, there are almost no wet sheet products in practical use that can simultaneously impart antifouling and antibacterial (or antifungal) properties with excellent water resistance. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2006-307389 A [Patent Document 2] Special Publication No. 2011-30793 [Patent Document 3] Patent Publication No. 2021-172715 [Patent Document 4] JP 2022-118980 A [Patent Document 5] JP 2018-90564 A [Patent Document 6] JP 2019-112342 A [Patent Document 7] JP 2022-49134 A Summary of the Invention [Problem to be solved by the invention]
[0013] An object of the present invention is to provide a wet sheet that can impart water-resistant, sustained antifouling, antiviral, antibacterial, antifungal, and the like to objects made of any material that are exposed to rain and face the outdoors, such as window panes, screen doors, blinds, vehicle covers, tents, and eaves tents, as well as objects that are exposed to water on a daily basis inside a residence, such as shower curtains in modular baths, toilets, kitchen sinks, wash basins, and bathroom walls.
[0014] In particular, the object is to provide a sheet-like cleaning article that can impart water-resistant, long-lasting antifouling, antiviral, antibacterial, antifungal, etc. properties to objects made of hydrophobic materials such as plastic. [Means for solving the problem]
[0015] The present invention can be expressed, for example, as follows. a) Water-soluble polymer having a carboxylic acid and / or a salt thereof: 0.05 to 5% by weight b) Antibacterial agents and / or bactericides having cationic groups: 0.1 to 10% by weight c) Electrolyte: 0.1~15% by weight The present invention relates to a sheet-like cleaning article for imparting antifouling and / or antibacterial properties to a surface of an object, the sheet-like substrate being impregnated with a liquid composition containing the above-mentioned formula (I), and the pH of the liquid composition in the sheet-like substrate is in the range of 3 to 12. Effect of the Invention
[0016] According to the present invention, the surface of the object to be treated can be made to have the following properties: inhibition of adhesion of dirt, easy rinsability of dirt, and / or antibacterial properties, even in a situation where water (rainwater) is splashed on the object to be treated, regardless of whether the object is made of hydrophilic or hydrophobic material, hard or soft material. The term "easy rinsability" as used herein means that dirt adhering to the object can be rinsed away by splashing water or rain. The term "antibacterial properties" as used herein means the function of inhibiting bacteria from adhering to the surface and multiplying when moisture and a nutrient source are present. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] (1) The sheet-like cleaning item of the present invention is a) Water-soluble polymer having a carboxylic acid and / or a salt thereof: 0.05 to 5% by weight b) Antibacterial agents and / or bactericides having cationic groups: 0.1 to 10% by weight c) Electrolyte: 0.1~15% by weight The liquid composition containing the above-mentioned is impregnated into a sheet-like substrate, and the pH of the liquid composition in the sheet-like substrate is in the range of 3 to 12.
[0018] (2) Water-soluble polymer having carboxylic acid and / or its salt
[0019] (2-1) In the present invention, it is the "a) water-soluble polymer having a carboxylic acid and / or a salt thereof" that exhibits the function of inhibiting adhesion of dirt (e.g., mud, soot, sebum, soap scum, etc.) and the function of rinsing easily. It is presumed that when this water-soluble polymer remains on the surface of an object, the negative charge of the carboxylic acid and / or a salt thereof in the water-soluble polymer brings about hydrophilization of the surface of the object.
[0020] Various water-soluble polymers having carboxylic acid and / or its salt can be used. Examples of natural polymers include xanthan gum, pectin, gellan gum, diutan gum, welan gum, gum arabic, hyaluronic acid, tragacanth gum, succinoglycan, sodium (potassium) alginate, examples of semi-synthetic polymers include sodium (potassium) carboxymethylcellulose and sodium (potassium) carboxyethylcellulose, examples of synthetic polymers include sodium salt (potassium salt) of carboxyvinyl polymer, sodium (potassium) polyacrylate, and modified polyvinyl alcohol having carboxylate.
[0021] Among these, xanthan gum, gellan gum, diutan gum, succinoglycan, and carboxymethylcellulose are preferred, and among these, xanthan gum is more preferred.
[0022] It was not previously known that water-soluble polymers having these carboxylic acids and / or salts thereof can modify the surfaces of hydrophilic objects such as glass, ceramics, wood, and cotton fiber articles, as well as hydrophobic objects such as screen doors, shower curtains, vehicle covers, shutters, sinks, and bathroom walls, thereby exhibiting excellent stain resistance and easy rinsability.
[0023] (2-2) It is possible to leave the water-soluble polymer on the surface of an object by wiping with a sheet-like cleaning article impregnated with a liquid composition containing a water-soluble polymer having a carboxylic acid and / or a salt thereof, but when the surface of the object is exposed to rainwater or water, the water-soluble polymer will wash off the surface of the object, resulting in a loss of the antifouling function (inhibition of adhesion of dirt, easy rinsing of dirt). However, by using the above-mentioned "b) antibacterial agent and / or bactericide having a cationic group" in combination, the carboxylic acid and / or a salt thereof can be fixed to the surface of the object even when the surface of the object is exposed to rainwater or water, and the function of inhibiting adhesion of dirt and easy rinsing associated with the hydrophilization of the surface of the object can be continuously exerted.
[0024] However, when a water-soluble polymer having a carboxylic acid and / or its salt is used in combination with a significant amount of the antibacterial agent and / or bactericide having a cationic group, an insoluble complex is immediately formed, and a homogeneous liquid composition is not obtained, so that even if the sheet-like substrate is impregnated with the composition, it is difficult to exhibit the function of inhibiting dirt adhesion by wiping or the function of easy rinsing. Therefore, it is necessary to further contain the above-mentioned "c) electrolyte".
[0025] In the liquid composition of the present invention, the water-soluble polymer having a carboxylic acid and / or its salt and the antibacterial agent and / or bactericide having a cationic group are dissolved or dispersed uniformly without forming insoluble matter due to the action of the electrolyte. Furthermore, even if this liquid composition is impregnated into a sheet-like substrate, the liquid composition in the sheet-like substrate (i.e., impregnated into the sheet-like substrate) is retained without being destabilized, and when the sheet-like substrate is used as a sheet-like cleaning article to wipe an object, the liquid composition is released from the sheet-like substrate and applied to the surface of the object in a coating or other manner. The liquid composition can also be applied to the surface of the object in a manner other than wiping.
[0026] The non-volatile components in the liquid composition of the present invention, which are applied to the surface of the object by coating or the like as described above, remain on the surface of the object by drying or the like. Furthermore, when the surface of the object is exposed to rainwater or water, the antibacterial agent and / or bactericide having a cationic group in the non-volatile components and the water-soluble polymer having a carboxylic acid and / or its salt form a complex, which is insolubilized and fixed to the surface of the object. This allows the antifouling properties (inhibition of adhesion of dirt, easy rinsing of dirt) to be sustained even on an object surface that is continuously or repeatedly exposed to rainwater or water. On the other hand, the non-volatile components (e.g., non-ionic surfactants, solvents, electrolytes, etc.) that are not involved in the formation of the complex will flow off the surface of the object by rainwater or water, or at least will easily flow off.
[0027] Such an anti-fouling function means a reduction in organic soiling, which serves as nutrients for bacteria and fungi to grow on the surface of the target object, and improves the function of imparting antibacterial and even antifungal properties to the surface of the target object, which is the objective of the present invention.
[0028] (2-3) Examples of materials that can be wiped with the sheet-like cleaning article of the present invention include the surfaces of hard materials such as hydrophilic hard plates, fabrics or films, and laminates thereof, such as ceramic tiles, ceramics, glass, enamel, cellulose (cotton, rayon, cellophane, etc.) and wood, as well as the surfaces of hydrophobic hard plates, fabrics or films, and laminates thereof, such as plastics (synthetic resins) such as acrylic resins (acrylic acid ester resins, methacrylic acid ester resins, etc.), polyester resins (polyethylene terephthalate resins, etc.), and polyvinyl chloride resins, such as stainless steel, but are not limited to these.
[0029] (2-4) The concentration of “a) the water-soluble polymer having a carboxylic acid and / or a salt thereof” in the liquid composition of the present invention is 0.05 to 5% by weight.
[0030] If the content is less than 0.05% by weight, sufficient inhibition of adhesion of dirt (especially sebum dirt) and easy rinsing are not achieved. If the content exceeds 5.0% by weight, the viscosity becomes too high, and the handling properties of the liquid composition are impaired. The content is preferably 0.1 to 3% by weight, more preferably 0.2 to 1% by weight, and even more preferably 0.25 to 0.7% by weight.
[0031] (2-5) Among the water-soluble polymers having a carboxylic acid and / or a salt thereof, particularly preferred xanthan gum has a property of exhibiting high viscosity at low concentrations, while having a property of rapidly decreasing viscosity when shear force is applied during stirring, etc. Therefore, a liquid composition containing xanthan gum can be smoothly released from an impregnated sheet-like substrate, or applied to the surface of an object in other ways, or applied in other ways. In addition, it exhibits properties such as components being likely to remain on vertical surfaces or parts along vertical surfaces, such as walls, curtains, window panes, screens, blinds, and storm shutters. In other words, it promotes the expression of functions such as cleanability, antifouling property, and antibacterial property from the viewpoint of easy application due to fixation to the surface of the object or release of the liquid composition from the sheet.
[0032] (3) Antibacterial and / or bactericidal agents having cationic groups
[0033] (3-1) In the present invention, it is the above-mentioned "b) antibacterial agent and / or bactericide having a cationic group" that exhibits antibacterial properties.
[0034] Antibacterial and / or bactericidal agents having a cationic group are bases that become cationic in water, but do not include amphoteric bases that have both cationic and anionic properties in one molecule.
[0035] The concentration of "b) antibacterial agent and / or bactericide having a cationic group" in the liquid composition of the present invention is 0.1 to 10% by weight. If it is less than 0.1% by weight, the antibacterial properties are not fully exhibited. If it exceeds 10.0% by weight, it becomes an excessive amount. It is preferably 0.2 to 7% by weight, more preferably 0.3 to 3% by weight, and even more preferably 0.4 to 2% by weight.
[0036] (3-2) Antibacterial agents and / or bactericides having a cationic group are already used in various cleaning agents, and provide effects such as sterilization, disinfection, sterilization, antibacterial properties, and antifungal properties by killing bacteria or fungi present on the surface of objects. It is said that antibacterial agents and / or bactericides having a cationic group adsorb and penetrate the cell membrane of bacteria or fungi, destroying the cell membrane or inactivating cell membrane proteins, thereby killing the bacteria or fungi.
[0037] These effects are exhibited when the liquid composition released from the sheet-like cleaning article of the present invention comes into contact with bacteria or fungi for a certain period of time, and also acts on viruses to inactivate them.
[0038] By the way, when the surface of an object is treated by wiping with a sheet-like cleaning article impregnated with a liquid composition containing an antibacterial agent and / or bactericide having a cationic group having the above-mentioned bactericidal action, the antibacterial agent and / or bactericide having a cationic group contained in the cleaning agent is a non-volatile component, so it can remain on the surface of the object and exhibit antibacterial and / or antifungal properties. However, when rainwater or water is splashed on the surface of the object, the cationic base will flow off the surface of the object, or at least it is easy to flow off, making it difficult to exhibit sustained antibacterial and / or antifungal properties. For example, it is almost impossible to exhibit and maintain sustained antibacterial and / or antifungal properties on the surface of objects that are frequently splashed with water or rainwater, such as kitchen sinks, bathrooms, shower curtains, washstands, glass, screen doors, blinds, sashes, shutters, car covers, etc.
[0039] The inventors have produced a sheet-like cleaning article impregnated with a liquid composition obtained by combining an antibacterial agent and / or bactericide having a cationic group with a water-soluble polymer having a carboxylic acid and / or its salt, and further mixing the liquid composition homogeneously with an electrolyte, thereby making it possible to fix the antibacterial agent and / or bactericide having a cationic group to any target surface, such as a hard surface or fabric surface, without running off even when water or rainwater is applied to the surface. This allows antibacterial properties to be imparted to the target surface that is continuously exposed to rainwater or water. In addition to antibacterial properties, the target surface may also be imparted with antifungal properties. The antifungal properties referred to here refer to the function of suppressing fungi from growing when the fungi adhere to the surface and are present in the presence of moisture and nutrient sources.
[0040] In addition, antibacterial agents and / or bactericides having a cationic group are considered to have the effect of easily decomposing the dirt by causing a substitution reaction with the metal ions of fatty acid metal salts called soap scum, which is a typical dirt on bathrooms, washstands, sinks, etc., and are therefore excellent cleaning bases in this respect as well.Furthermore, they also have the effect of weakening the adhesive force of oily dirt adhering to the surfaces of various objects, making it easier to remove the dirt from the surfaces of the objects.
[0041] (3-3) The "b) antibacterial agent and / or bactericide having a cationic group" in the present invention is preferably, but not limited to, 1) a cationic surfactant, 2) a cationic polymer, or 3) a guanidine skeleton or biguanide skeleton compound.
[0042] As the cationic surfactant of 1) above, cationic surfactants of alkylamine salt type or alkenylamine salt type, quaternary ammonium salt type, and pyridine ring salt type are preferable, but are not limited thereto. The cationic surfactant may be used alone or in combination of two or more.
[0043] (i) As the alkylamine salt type and alkenylamine salt type, monoalkyl (or alkenyl)amines, dialkyl (or dialkenyl)amines, and trialkyl (or trialkenyl)amines are preferred.
[0044] The number of carbon atoms in the alkyl group in the alkylamine salt type (or the alkenyl group in the alkenylamine salt type) is preferably 6 to 20, and more preferably 10 to 18. The alkyl group (or alkenyl group) can be linear or branched, but is preferably linear. A preferred example is N-(3-aminopropyl)-N-dodecylpropane-1,3-diamine (product name: LONZABAC12 ["LONZABAC" is a trademark], manufactured by LONZA).
[0045] (ii) As the quaternary ammonium salt type, tetraalkyl (or tetraalkenyl) ammonium salts or benzyltrialkyl (or trialkenyl) ammonium salts are preferred.
[0046] The number of carbon atoms of the alkyl group or alkenyl group in the quaternary ammonium salt type is preferably 6 to 20. More preferably, the number of carbon atoms is 8 to 18. The alkyl group (or alkenyl group) can be linear or branched, but is preferably linear. Preferable specific examples include dodecyltrimethylquaternary ammonium chloride, tetradecyltrimethylquaternary ammonium chloride, hexadecyltrimethylquaternary ammonium chloride, coconut alkyltrimethylquaternary ammonium salt, palm oil or palm kernel oil alkyltrimethylquaternary ammonium salt, tallow alkyltrimethylquaternary ammonium salt, benzalkonium chloride having an alkyl group of 8 to 18 carbon atoms, benzethonium chloride, dialkyldimethylammonium salt having 8 to 10 carbon atoms, dioctyldimethylammonium salt, didecyldimethylammonium salt, N,N-didecyl-N-methylpoly(oxyethyl)ammonium propionate salt, monoalkyltrimethylammonium salt, dialkyldimethylammonium salt, and the like.
[0047] (iii) As the pyridine ring salt-containing type, alkyl (or alkenyl) pyridinium salts are preferred. The number of carbon atoms in the alkyl (or alkenyl) group is preferably 6 to 20, and more preferably 10 to 18. A preferred example is cetylpyridinium chloride.
[0048] As for the cationic polymer of 2) above, a cationic polymer having a quaternary ammonium salt in the main chain or side chain, a cationic polymer having a guanidine skeleton or a biguanide skeleton in the main chain or side chain, a cationic polymer having an amine in the main chain, or a cationic polymer having an amino group in the side chain is preferred.
[0049] A specific example of a cationic polymer having a quaternary ammonium salt in the main chain is N,N-dimethyl-2-propylammonium chloride polymer (product name: Barquat PQ ["Barquat" is a trademark], manufactured by LONZA). A specific example of a cationic polymer having a quaternary ammonium salt in the side chain is diallyldimethylammonium chloride polymer (product name: Merquat 100 ["Merquat" is a trademark], manufactured by Lubrizol), and a copolymer consisting of diallyldimethylammonium chloride and acrylamide (product name: Merquat 550 ["Merquat" is a trademark], manufactured by Lubrizol). An example of a cationic polymer having an amine in the main chain is polyethyleneimine. An example of a cationic polymer having an amino group in the side chain is ε-poly-L-lysine, in which the amino acid lysine is linked by an amide bond. Products made by fermentation are commercially available. In addition, an example of a cationic polymer consisting of β1→4 bonds of glucosamine is chitosan. Industrially, chitosan is produced by deacetylating chitin (poly-β1→4-N-acetylglucosamine) obtained from crustaceans such as crabs and shrimp by boiling in concentrated alkali. The conversion of chitin to chitosan (deacetylation) is not complete, and in some cases about 30% of chitin remains in chitosan.
[0050] Specific examples of cationic polymers having a guanidine skeleton or a biguanide skeleton include polyhexamethylene guanidine or a salt thereof (e.g., phosphate), polyhexamethylene biguanide or a salt thereof, such as hydrochloride (an example of a hydrochloride product: Proxel IB [trade name, "Proxel" is a trademark, manufactured by LONZA, Inc., the same applies below]). Other examples include polyaminopropyl biguanide or a salt thereof (e.g., hydrochloride). Among these, polyhexamethylene guanidine or polyhexamethylene biguanide is particularly preferred.
[0051] The guanidine skeleton or biguanide skeleton compound in 3) above is a non-polymeric guanidine skeleton or biguanide skeleton compound, i.e., excluding the above-mentioned cationic polymers having a guanidine skeleton or biguanide skeleton, and specific examples thereof include chlorhexidine or a salt thereof, such as a gluconate salt such as chlorhexidine gluconate (trade name: Spectradyne ["Spectradyne" is a trademark], manufactured by LONZA), hydrochloride, acetate, etc. Also included is alexidine hydrochloride.
[0052] In particular, in residential spaces such as kitchen sinks, bathrooms, and washstands, warm water is generally used not only for rinsing during cleaning operations, but also for washing dishes and taking a bath, and long periods of rainfall are associated with window glass, screen doors, blinds, shutters, vehicle covers, tents, and the like, and even in such usage environments, cationic polymers or compounds having a guanidine skeleton or biguanide skeleton can impart excellent antibacterial properties to the surface of the object, and can also impart antifungal properties in addition to antibacterial properties to the surface of the object.
[0053] (4) Electrolyte
[0054] (4-1) The liquid composition of the present invention contains “c) an electrolyte”.
[0055] As described above, when a water-soluble polymer having a carboxylic acid and / or its salt is mixed with an antibacterial agent and / or bactericide having a cationic group, a complex is formed due to electrostatic interaction, and insoluble matter is generated, resulting in a non-uniform composition that cannot perform various functions. Therefore, in order to suppress the generation of insoluble matter due to the formation of a complex and to enable the mixture to be mixed in a uniform state, the liquid composition needs to contain a required amount of electrolyte.
[0056] The concentration of "c) electrolyte" in the liquid composition of the present invention is 0.1 to 15% by weight, and depends on the concentration of the water-soluble polymer having a carboxylic acid and / or its salt and the antibacterial agent and / or bactericide having a cationic group, and is preferably 0.5 to 12% by weight, more preferably 1 to 10% by weight, and even more preferably 2 to 9% by weight.
[0057] The pH of the liquid composition in the sheet-like substrate of the present invention is 3 to 12. The pH of the liquid composition in the sheet-like substrate is determined by applying pressure to the sheet-like cleaning article and measuring the pH of the liquid squeezed out. The pH is more preferably 4 to 12. By adjusting the pH to a level that allows use with bare hands, the liquid composition can be used easily and safely without worrying about irritation to the skin, eyes, etc.
[0058] (4-2) Examples of the “c) electrolyte” in the present invention include inorganic acids and / or salts thereof, monovalent organic acids and / or salts thereof, and polycarboxylic acids, polyphosphonic acids, and polyphosphoric acids, each of which has a metal chelating ability (i.e., divalent or higher carboxylic acids, phosphonic acids, and phosphoric acids, each of which has a bidentate or higher ligand that bonds with a metal ion to form a chelate compound) and / or their salts.
[0059] (4-3) Preferable examples of inorganic acids and / or their salts include hydrochloric acid, sulfuric acid, carbonic acid, phosphoric acid, and silicic acid, as well as their respective alkali metal salts, alkaline earth metal salts, and zinc salts. Considering that the pH of the final liquid composition is 3 to 12, it is preferable to mainly use inorganic salts.
[0060] (4-4) Preferred examples of monovalent organic acids and / or salts thereof include formic acid, acetic acid, lactic acid, propionic acid, fatty acids having more carbon atoms than these, and benzoic acid, as well as their respective alkali metal salts, alkaline earth metal salts, and zinc salts.
[0061] (4-5) Preferred examples of polycarboxylic acids and / or their salts having metal chelating ability (polycarboxylic acid-based metal chelating agents) include malonic acid, succinic acid, glutaric acid, gluconic acid, malic acid, citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, diethylenetriaminepentaacetic acid, hydroxyethylethylenetriacetic acid, and hydroxyethyliminodiacetic acid, as well as their salts (e.g., sodium salts). Particularly preferred examples include trisodium citrate and sodium ethylenediaminetetraacetate.
[0062] (4-6) Preferred examples of polyphosphonic acids and / or their salts having metal chelating ability (polyphosphonic acid-based metal chelating agents) include ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, ethanehydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, aminopolymethylenephosphonic acid, polyethylenepolyaminepolymethylenephosphonic acid, ethylenediaminetetramethylenephosphonic acid, and their respective salts. Examples of the salts include alkali metal salts such as sodium and potassium, ammonium salts, and alkanolamine salts such as monoethanolamine and triethanolamine.
[0063] (4-7) Preferred examples of polyphosphoric acid and / or a salt thereof having metal chelating ability (polyphosphate-based metal chelating agent) include metaphosphoric acid, orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, hexametaphosphoric acid, and their respective salts.
[0064] The "electrolyte" may be any one of the above, or may be a combination of two or more of the above.
[0065] (5) Examples of components other than a), b) and c) that may be contained in the liquid composition of the present invention
[0066] (5-1) In the present invention, in addition to the antibacterial agent and / or bactericide having a cationic group, it is preferable to use a nonionic surfactant or an amphoteric surfactant from the viewpoint of improving the cleaning properties and finish during treatment such as wiping with the sheet-like cleaning article.
[0067] (i) The nonionic surfactant is preferably at least one selected from polyoxyethylene alkyl ethers, polyoxyethylene alkenyl ethers, polyoxyethylene branched alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxypropylene alkyl ethers, polyoxypropylene alkenyl ethers, polyoxyethylene polypropylene alkyl ethers, polyoxybutylene alkyl ethers, polyoxybutylene alkenyl ethers, sucrose fatty acid esters, aliphatic alkanolamides, fatty acid glycerin monoesters, and alkyl glycosides. The number of carbon atoms in the alkyl or alkenyl group in these nonionic surfactants is preferably 8 to 18.
[0068] Among these, alkyl glucosides are particularly preferred from the viewpoints of mixing stability of the liquid composition and finishing quality of treatment such as wiping. Specific examples include those represented by the following formula (I). R 1 -(OR 2 )nGm ....(I) [In formula (I), R 1 is an alkyl group having 8 to 18 carbon atoms, R 2 represents an alkylene group having 2 to 4 carbon atoms, G represents a group derived from a reducing sugar, n represents the average number of moles added (0 to 5), and m represents the average degree of condensation (1 to 3). The reducing sugar may be either an aldose or a ketose, but is preferably glucose.]
[0069] Examples of alkyl glucosides include octyl polyglucoside, 2-ethylhexyl polyglucoside, decyl polyglucoside, lauryl polyglucoside, myristyl polyglucoside, palmityl polyglucoside, stearyl polyglucoside, and oleyl polyglucoside. Among these, alkyl glucosides having an alkyl group with 14 or less carbon atoms are particularly preferred.
[0070] The alkyl glucoside is preferably contained in the liquid composition of the present invention in an amount of 0.5 to 10% by weight. If it is less than 0.5% by weight, the mixing stability of the liquid composition and the finish of wiping, etc. are insufficient. In addition, when exposed to rainwater or water after wiping, etc., the surface on which the non-volatile matter remains is less likely to generate aggregates, resulting in a better finish. If it exceeds 10% by weight, foaming, etc. during wiping, etc. becomes noticeable, which may cause negative aspects in the finish.
[0071] (ii) Preferred examples of amphoteric surfactants include alkylamine oxides, alkenylamine oxides, alkylamidopropyl-N,N-dimethylacetate betaine, alkylamidopropyl-N,N-dimethyl-2-hydroxypropylsulfobetaine, and alkylamidopropyl-N,N-dimethyl-propylsulfobetaine.
[0072] More specific examples of preferred amphoteric surfactants include laurylamine oxide, myristylamine oxide, lauric acid amidopropyl-N,N-dimethyl acetate betaine, myristate amidopropyl-N,N-dimethyl acetate betaine, cocamidopropyl-N,N-dimethyl acetate betaine, and lauryl hydroxysulfobetaine.
[0073] (iii) The liquid composition of the present invention may also contain an anionic surfactant, if necessary. Specific examples of the anionic surfactant that may be contained include alkyl ether sulfates, polyoxyalkylene alkyl ether sulfates, and fatty acid salts (soaps).
[0074] In addition, since anionic surfactants may form insoluble complexes with the above-mentioned "b) antibacterial agents and / or bactericides having cationic groups," it is necessary to suppress the formation of insoluble complexes by adding "c) electrolytes" to form a homogeneous liquid composition.
[0075] (5-2) The liquid composition of the present invention preferably contains a water-soluble solvent in order to provide the liquid composition with excellent uniform dissolution or uniform dispersion stability, and further from the viewpoint of improving the cleaning ability of oily stains. By containing a water-soluble solvent in the liquid composition of the present invention, the liquid composition has the effect of improving the stability of uniform dissolution or uniform dispersion even if the content of the electrolyte is reduced.
[0076] The liquid composition of the present invention may contain glycol and / or glycol ether (i.e., one or both of glycol and glycol ether) as a water-soluble solvent. For example, the liquid composition may contain 2 to 30% by weight of glycol and / or glycol ether (when both glycol and glycol ether are contained, the total of both is 2 to 30% by weight).
[0077] Specific examples of glycol ethers as the water-soluble solvent include ethylene glycol monobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol monobutyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monoisobutyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol dimethyl ether, polyoxyethylene polyoxypropylene glycol dimethyl ether, polyoxyethylene glycol phenyl ether, phenyl carbitol, phenyl cellosolve, benzyl carbitol, and hexylene glycol. Among these, propylene glycol monomethyl ether, diethylene glycol monobutyl ether, dipropylene glycol monobutyl ether, and hexylene glycol are preferred from the viewpoints of detergency, odor, and feel. Among these, diethylene glycol monobutyl ether is particularly preferred.
[0078] The water-soluble solvent is preferably contained in the liquid composition of the present invention in an amount of 2 to 30% by weight. If it is less than 2%, the cleaning power for oily dirt is not fully exhibited, and if it exceeds 30% by weight, the hands may feel degreased or the odor may be unpleasant. More preferably, it is 3 to 20% by weight, and even more preferably, 5 to 15% by weight.
[0079] The viscosity of the liquid composition of the present invention is preferably in the range of 20 to 800 mPa·s. If it is less than 20 mPa·s, the components are easily washed away when exposed to rainwater or water, and if it exceeds 800 mPa·s, it becomes difficult to apply the composition widely and uniformly to the target surface when wiping with a wet sheet (sheet-type cleaning product). Furthermore, the range of 50 to 650 mPa·s is preferable, and the range of 70 to 500 mPa·s is particularly preferable. The viscosity of the liquid composition is in the range of values measured by a B-type viscometer (TVB-10M, manufactured by Toki Sangyo Co., Ltd.) using a TM2 rotor or TM3 rotor at a speed of 60 revolutions (rpm).
[0080] (5-3) In addition, the liquid composition of the present invention may contain 0.5 to 5% by weight of an alkaline agent such as alkanolamine to improve the cleaning properties of solidified or denatured oily dirt, 0.5 to 10% by weight of ethanol or isopropyl alcohol to improve the refreshing feeling and adjust the viscosity of the cleaner, and may further contain bactericides, preservatives, deodorants, fragrances, colorants, pigments, thickeners other than water-soluble polymers having carboxylic acids and / or salts thereof, water, etc. As deodorants, about 0.1 to 5% by weight may be contained, and for example, green tea extract, cyclodextrin, etc. are preferable.
[0081] (6) Sheet-like substrate
[0082] The sheet-like substrate in the present invention may be any substrate capable of impregnating and retaining the liquid composition.
[0083] The sheet-like substrate may be selected from, but is not necessarily limited to, paper, nonwoven fabric, woven fabric, a composite substrate of paper and nonwoven fabric, a composite substrate of nonwoven fabric and woven fabric, and a composite substrate of paper and film, nonwoven fabric and film, woven fabric and film, or paper, nonwoven fabric and film.
[0084] The basis weight of the sheet-like substrate is 30 g / m 2 ~200g / m 2 is preferred. 2If the density is lower than 200 g / m, the amount of the liquid composition supplied to a target surface having a certain area is small. 2 If it is higher, problems are likely to occur in terms of fitting to the target surface.
[0085] The paper refers to a sheet made by a wet papermaking method using pulp, rayon fiber, or synthetic fiber as the main raw material, and examples of the paper include those that have been spunlaced or have multiple sheets laminated by embossing, etc. Also included is water-degradable paper that contains water-soluble binders and can be disposed of by flushing the toilet.
[0086] Examples of the nonwoven fabric include nonwoven fabrics manufactured by a dry thermal bond method in which web formation is performed dry, a dry resin method, a dry spunlace method, a dry needle punch method, an air-laid resin bond method, an air-laid thermal bond method, etc. Among these, from the viewpoints of wiping comfort and dirt absorbency, the dry spunlace method, the air-laid resin bond method, the air-laid thermal bond method, etc. are preferred.
[0087] Other examples include nonwoven fabrics produced by the spunbond method or meltblown method using continuous long fibers.
[0088] An example of the sheet-like substrate is a woven fabric.
[0089] The above-mentioned paper or nonwoven fabric includes a single layer, a laminate, or a composite of these, and further includes sheet-like substrates with a laminated structure in which a film of cellophane, polyvinyl alcohol (PVA), polyester, polyolefin, polyvinylidene chloride, or the like is laminated to the above.
[0090] The impregnation amount of the liquid composition in the sheet-like substrate is 1.5 to 10 times the weight of the sheet-like substrate. If it is less than 1.5 times, the amount of the liquid composition supplied by release, etc. to a target surface having a certain area is small, and if it is more than 10 times, the amount of the liquid composition supplied by release, etc. at the beginning of wiping may be too large. It is more preferably 2 to 7 times.
[0091] The material of the sheet-like substrate preferably has a cellulose fiber content of less than 40% by weight. If the cellulose fiber content exceeds 40% by weight, the antibacterial agent and / or bactericide having a cationic group in the liquid composition to be impregnated may be adsorbed and held by the negatively charged cellulose fibers, depending on the amount of impregnation. This may result in a decrease in the amount of the antibacterial agent and / or bactericide having a cationic group that is supplied to the target surface by release or the like during treatment such as wiping.
[0092] Therefore, the sheet-like substrate of the present invention preferably contains hydrophobic fibers in an amount of 60% or more. Examples of the hydrophobic fibers include polyolefin fibers, polyester fibers, polystyrene fibers, acrylic fibers, and nylon fibers. EXAMPLES
[0093] Examples 1 and 2
[0094] As a water-soluble polymer having a carboxylic acid and / or a salt thereof, xanthan gum (product name: KELZAN AR ["KELZAN" is a trademark], manufactured by CP KELCO) was used. As the antibacterial agent and / or bactericide having a cationic group, a cationic surfactant is Coconut alkyl benzyl dimethyl ammonium chloride (benzalkonium chloride, product name: Hyamine 3500J), Dodecyltrimethylammonium chloride (product name: Nissan Cation BB ["Nissan Cation" is a trademark], manufactured by NOF Corporation), and Polyhexamethylene biguanide (trade name: Proxel IB), a cationic polymer antibacterial agent having a biguanide skeleton, The electrolyte is a polycarboxylic acid and / or its salt having metal chelating ability. Trisodium citrate (anhydrous) (reagent, manufactured by Wako Pure Chemical Industries, Ltd.), Sodium ethylenediaminetetraacetate (EDTA-4Na) (reagent, manufactured by Wako Pure Chemical Industries, Ltd.), and Citric acid (anhydrous) (reagent, manufactured by Wako Pure Chemical Industries, Ltd.) of, Other surfactants include lauryl glucoside (product name: Mydol 12, ["Mydol" is a trademark], manufactured by Kao Corporation); As a water-soluble solvent, diethylene glycol monobutyl ether (product name: Butyl Diglycol NO) was used. The liquid compositions shown in Table 1 (Table 2) were prepared (Example 1 and Example 2 had the same composition). The values of each component shown in Table 1 (and Table 2) are in weight percent.
[0095] The appearance of the obtained liquid composition was observed, and the pH and viscosity were measured. The viscosity of the liquid composition was measured using a B-type viscometer (TVB-10M, manufactured by Toki Sangyo Co., Ltd.) with a TM2 rotor or a TM3 rotor at a rotation speed (rpm) of 60.
[0096] Example 1
[0097] Spunlace nonwoven fabric made of 100% polyester fiber (weight: 45g / m 2 A sheet-like substrate (weight: 2.7 g) was prepared as a sheet-like substrate (size: 30 cm x 20 cm), and the liquid composition was impregnated into the sheet-like substrate (weight: 2.7 g) so that the weight of the liquid composition impregnated was 2.7 times the weight of the sheet-like substrate, to prepare a sheet-like cleaning article.
[0098] After 24 hours from the immersion, the sheet-like cleaning article was squeezed, and the pH of the collected squeezed liquid was measured.
[0099] Thereafter, an antifouling test (carbon black removal test by water spray) and an antibacterial test were carried out on an acrylic plate, a screen door net, and a transparent glass plate that had been wiped with the sheet-like cleaning article.
[0100] In addition, a mold resistance test and a water wettability test were carried out on the acrylic plate that had been wiped with the sheet-like cleaning article.
[0101] The results of tests other than the water wettability test are shown in Table 1, and the results of the water wettability test are shown in Table 2.
[0102] Example 2
[0103] Spunlace nonwoven fabric made of 100% polyester fiber (weight: 45g / m 2 The size is 30cm x 20cm. The fabric is a spunlace nonwoven fabric (weight: 45g / m2) made of polyester fiber / rayon fiber = 70 / 30 (weight%). 2 The same treatment as in Example 1 was carried out except that the squeezed liquid was changed to a different size (size: 30 cm x 20 cm), the pH of the squeezed liquid was measured, and a stain resistance test, an antibacterial test, a mold resistance test, and a water wettability test were carried out.
[0104] The results are shown in Tables 1 and 2.
[0105] Comparative Example 1
[0106] The same procedure as in Example 1 was repeated except that xanthan gum was not added to the liquid composition, and the pH of the squeezed liquid was measured, and a stain resistance test, antibacterial test, mold resistance test, and water wettability test were carried out.
[0107] The results are shown in Tables 1 and 2.
[0108] Comparative Example 2
[0109] The same procedure as in Example 1 was repeated except that coconut alkylbenzyldimethylammonium chloride (benzalkonium chloride), dodecyltrimethylammonium chloride, and polyhexamethylene biguanide were not added to the liquid composition, and the pH of the squeezed liquid was measured, and a stain resistance test, antibacterial test, mold resistance test, and water wettability test were performed.
[0110] The results are shown in Tables 1 and 2.
[0111] Antifouling test <Carbon black removal test by water spray>
[0112] (Test Method)
[0113] A white acrylic plate (manufactured by Hyoshin, an acrylic specialty store) measuring 200 mm x 200 mm x 2 mm (length x width x thickness), a screen net (Crown Net #24 24 mesh (mesh size: 0.84 mm, made of polypropylene) measuring 200 mm x 200 mm (length x width x thickness), and a transparent glass plate (soda-lime glass manufactured by AS ONE) measuring 200 mm x 200 mm x 5 mm (length x width x thickness) were prepared in multiple sheets for each of Examples 1 and 2, Comparative Examples 1 and 2, and an untreated plate (blank).
[0114] For each of the Examples and Comparative Examples, the front and back surfaces (20 cm x 20 cm surfaces) of each acrylic plate, screen net, and transparent glass plate were wiped back and forth twice on each side with a sheet-like cleaning item impregnated with the liquid composition of each of the Examples and Comparative Examples, and then dried for 10 minutes in a constant temperature dryer maintained at 50°C.
[0115] After drying, the acrylic plates, the screen nets, and the transparent glass plates of Examples 1 and 2 and Comparative Examples 1 and 2 were each divided into two groups. One group was used for the carbon black removal test, and the other group was immersed for 10 minutes in 5 L of tap water contained in a plastic case with inner dimensions of 38 cm x 29 cm x depth of 8 cm to reflect the conditions where the plates are exposed to rain or water during use, and then removed from the tap water and dried for 10 minutes in a thermostatic dryer maintained at 50°C before being used for the carbon black removal test.
[0116] Before proceeding to the carbon black removal test operation, the weight (A) of each of the acrylic plate, the screen door net, and the transparent glass plate obtained by the above treatment was measured using a balance capable of measuring to the nearest 0.001 g.
[0117] Carbon black (MA100 manufactured by Mitsubishi Chemical Corporation) was used as a model stain, and 5,000 g of this was weighed out on a balance and placed in a plastic bag with a zipper (Unipack J-4 340 mm x 240 mm).
[0118] The acrylic plate, the screen net, and the transparent glass plate (each of which is called the "sample plate") that had been subjected to the above-mentioned wiping and drying treatment, or wiping and drying → soaking in water → drying treatment, were placed in a plastic bag with a zipper containing carbon black, and the sample plate was shaken by hand to ensure that the carbon black was evenly adhered to the front and back surfaces of the sample plate. When the sample plate was removed from the plastic bag, the sample plate was lightly shaken to remove any excess carbon black.
[0119] The weight (B) of the removed sample plate (with carbon black attached thereto) was measured using the balance.
[0120] The sample plate with carbon black attached was suspended in the air so that the front and back sides were vertical. Using a commercially available trigger spray container (Condor C Spray Container 500 ["Condor" is a trademark], manufactured by Yamazaki Sangyo Co., Ltd.) filled with tap water, 40 sprays (56 ml) were evenly sprayed onto the front side of the sample plate fixed in the air from a distance of 20 cm in the horizontal direction. Similarly, 40 sprays (56 ml) were evenly sprayed onto the back side from a distance of 20 cm in the horizontal direction. This spraying encouraged the carbon black attached to the front and back sides of the sample plate to flow off with the water. The sample plate was then allowed to dry naturally at room temperature.
[0121] In addition, for untreated (blank) acrylic plates, screen nets, and transparent glass plates that were not wiped with a sheet-like cleaning item impregnated with the liquid composition, the same operations were carried out from the point where carbon black was attached in a plastic bag with a zipper onwards.
[0122] The weight (C) of the sample plate after air drying was measured using the balance.
[0123] The amount of carbon black attached to the acrylic plate, the screen door net, and the transparent glass plate, and the removal rate of the carbon black that washed off and was removed by spraying water were calculated from the weights (A), (B), and (C) of the sample plate according to the following formula. The amount of carbon black attached and the removal rate were calculated in the same way for the untreated (blank) sample plate.
[0124] Carbon black adhesion amount = weight of sample plate after carbon black adhesion operation (B) - weight of sample plate before carbon black adhesion operation (A) Carbon black removal rate (%) = [amount of carbon black removed by water spray {weight (B) - weight (C)} / carbon black adhesion amount {weight (B) - weight (A)}] x 100 (%)
[0125] <Antibacterial Test>
[0126] The antibacterial testing and evaluation were carried out in accordance with JIS Z2801 antibacterial testing for plastic products.
[0127] (Test Method)
[0128] A 50 mm x 50 mm x 2 mm white acrylic plate (manufactured by Hyoshin, an acrylic specialty store), a 40 mm x 40 mm screen net [Crown Net #24 24 mesh (mesh size: 0.84 mm, made of polypropylene)], and a 50 mm x 50 mm x 2 mm transparent glass plate (as-one blue plate soda glass) were prepared in multiple pieces for each of Examples 1 and 2, Comparative Examples 1 and 2, and an untreated plate (blank).
[0129] For each of the Examples and Comparative Examples, the surface (50 mm x 50 mm surface) of each acrylic plate and transparent glass plate was wiped back and forth twice with a sheet-like cleaning article impregnated with the liquid composition of each of the Examples and Comparative Examples. The front and back surfaces (40 mm x 40 mm surface) of the screen net were wiped back and forth twice each with a sheet-like cleaning article impregnated with the liquid composition of each of the Examples and Comparative Examples.
[0130] Immediately afterwards, the acrylic plate and the transparent glass plate were placed in a sterile petri dish with the wiped surface facing up, and the screen netting was placed in a sterile dish with the later wiped surface facing up, and then dried for 12 hours in a constant temperature dryer maintained at 50°C.
[0131] After drying, the acrylic plates, the screen net, and the transparent glass plate of Examples 1 and 2 and Comparative Examples 1 and 2 were each divided into two groups. One group was used for the antibacterial test, and the other group was used for the antibacterial test. In order to reflect the conditions of rain and water during use, the acrylic plates and the transparent glass plate were immersed for 10 minutes in 350 ml of tap water in a glass container with inner dimensions of 10 cm x 10 cm x 5 cm, with the wiped surface of the acrylic plate and the screen net facing up, and the latter wiped surface of the screen net facing up. The acrylic plates, the screen net, and the transparent glass plate were then immediately placed in a sterilized petri dish with the wiped surface of the acrylic plate and the transparent glass plate facing up and the latter wiped surface of the screen net facing up, and dried for 12 hours in a thermostatic dryer maintained at 50°C, and then used for the antibacterial test.
[0132] In addition, for untreated (blank) acrylic plates, screen nets, and transparent glass plates that were not wiped with a sheet-like cleaning article impregnated with the liquid composition, they were dried for 12 hours in a constant temperature dryer maintained at 50°C, which corresponds to the drying process immediately after wiping, and the same operations as in the examples were then carried out to obtain untreated (blank) samples for each.
[0133] Equal amounts of Staphylococcus aureus (NBRC13276) and Escherichia coli (NBRC3972) were mixed and cultured in suspension in 3% nutrient bouillon, and then diluted 400-fold with saline to obtain a 2.5 × 10 5 ~1.0×106 A bacterial solution containing cfu / ml was prepared.
[0134] (Inoculation of bacterial liquid onto acrylic and transparent glass plates)
[0135] 0.4 ml of bacterial liquid was inoculated onto the wiped surfaces (only the surface was wiped) of the acrylic plate and transparent glass plate contained in the petri dish, and then a sterilized polypropylene film cut to a size of 40 mm x 40 mm was immediately placed on top of the plate and tightly adhered, after which the dish was sealed with a lid.
[0136] (Inoculation of bacteria onto screen netting)
[0137] The screen netting contained in the petri dish (both the front and back sides had been wiped) was placed on top of a sterilized polypropylene film cut to a size of 40 mm x 40 mm, 0.4 ml of bacterial liquid was inoculated onto the top surface of the screen netting, and then another sterilized polypropylene film of the same size was immediately placed on top of it, sandwiching the screen netting between the two polypropylene films, and the petri dish was then covered and sealed.
[0138] The test samples sealed in petri dishes were cultured for 24 hours in a thermostatic chamber set at 35°C and 90% humidity.
[0139] After 24 hours of incubation, the test piece still covered with the film was washed over the entire sample with 9.6 ml of saline using a pipette, thereby washing out the bacteria that had been cultured between the film and the sample into the saline.
[0140] 1.0 ml of each of the washed-out bacterial solution, a solution obtained by further diluting the bacterial solution 100-fold with physiological saline, and a solution obtained by diluting the bacterial solution 10,000-fold with physiological saline were smeared onto a petri dish containing SCDLP medium (Soybean Casein Digest Agar with Lecitin, polysorbate 80).
[0141] Thereafter, the mixture was cultured in a constant temperature bath at 37°C for 24 hours, and the number of colonies (viable bacteria count) was measured.
[0142] For the blank (untreated), the operations after inoculation of the bacterial liquid were carried out in the same manner as in the above-mentioned Examples and Comparative Examples, and the colony count (viable cell count) was measured.
[0143] From this antibacterial evaluation test, the antibacterial activity value was calculated based on the following formula. Antibacterial activity value: log [viable bacteria count on untreated (blank) test piece after 24 hours] - log [viable bacteria count on treated test piece after 24 hours]
[0144] <Antifungal test (acrylic plate)>
[0145] The same acrylic plates as those used in the antibacterial test were prepared for Examples 1 and 2, Comparative Examples 1 and 2, and an untreated plate (blank).
[0146] For each of the Examples and Comparative Examples, similarly to the antibacterial test, the surface was wiped back and forth twice with a sheet-like cleaning article impregnated with the liquid composition of each of the Examples and Comparative Examples.
[0147] Thereafter, the specimen was immediately placed in a sterile petri dish with the wiped surface facing up, and dried for 12 hours in a thermostatic dryer maintained at 50°C.
[0148] In order to reflect the conditions of exposure to rain and water during use, each of the acrylic sheets of Examples 1 and 2 and Comparative Examples 1 and 2 after drying was immersed for 10 minutes in 350 ml of tap water in a glass container with inner dimensions of 10 cm x 10 cm x 5 cm depth with the wiped surface facing up, and then the acrylic sheet was immediately taken out of the tap water and placed in a sterilized petri dish with the wiped surface facing up, dried for 12 hours in a thermostatic dryer maintained at 50°C, and then subjected to a mold resistance test. This test was performed on 5 of the same samples (N=5).
[0149] In addition, as for an untreated (blank) acrylic plate that was not wiped with a sheet-like cleaning material impregnated with the liquid composition, the same operations as in the examples were carried out after drying for 12 hours in a constant temperature dryer maintained at 50°C to obtain an untreated (blank) sample.
[0150] A mold resistance test was conducted on black mold (Cladosporium sphaerospermum NBRC 6348), which is often found to grow in dwellings, according to Method B (glucose-added inorganic salts agar medium) of the test method for plastic products in Appendix A of JIS Z2911:2018.
[0151] <Mold resistance test>
[0152] The spore suspension was prepared according to the method for preparing a single spore suspension in JIS Z2911:2018. Approximately 10 6 The concentration was adjusted to cfu / ml.
[0153] The glucose-added inorganic salt agar medium was aseptically dispensed into another petri dish to a thickness of about 5 mm and solidified, and the treated sample (50 mm x 50 mm x 2 mm white acrylic plate) contained in the petri dish was taken out on the medium and placed with the wiped surface facing up. Then, 0.1 ml of the spore suspension was inoculated onto the treated surface and agar medium using a sprayer, and the petri dish was sealed with a lid. The test was performed on the samples wiped with the sheet-like cleaning articles of Examples 1 and 2 and Comparative Examples 1 and 2, and on the untreated (blank) sample.
[0154] These test samples sealed in petri dishes were cultured in an incubator set at 24°C and 95% humidity for 4 weeks.
[0155] The samples cultured in this fungal resistance test were then observed initially with the naked eye and, if necessary, under a stereomicroscope.
[0156] The growth status of black mold (Cladosporium) was evaluated according to the following criteria in accordance with Appendix A of JIS Z2911:2018.
[0157] Mycelium growth rating: Mold growth status (0 to 5) No mold growth is visible to the naked eye or under a stereomicroscope. :0 Mold growth is not visible to the naked eye, but is clearly visible under a stereo microscope. Mold growth visible to the naked eye, covering less than 25% of the total surface area of the specimen: 2 Mold growth is visible to the naked eye and the area of the growth is 25% or more but less than 50% of the total area of the sample: 3 The mycelium is well developed and the area of the developed part is more than 50% of the total area of the sample: 4 The mycelium grows vigorously and covers the entire surface of the sample.
[0158] The results of the above tests and evaluations are shown in Table 1.
[0159] <Test evaluation of water wettability (acrylic plate)>
[0160] As hard-surface test plates, white acrylic plates measuring 50 mm×50 mm×2 mm (manufactured by Hyosin, an acrylic specialty store) were prepared for Examples 1 and 2, Comparative Examples 1 and 2, and an untreated plate (blank).
[0161] The surface of an acrylic plate (50 mm x 50 mm surface) was wiped twice with a sheet-like cleaning article impregnated with the liquid composition of the Examples and Comparative Examples, and then dried for 10 minutes in a thermostatic dryer maintained at 50°C with the wiped surface facing up.
[0162] Next, to reflect the conditions in which the dried acrylic plate will be exposed to rain or water during use, the plate was immersed for 10 minutes in 350 ml of tap water contained in a glass container with inner dimensions of 10 cm x 10 cm x 5 cm depth, with the wiped surface facing up. The acrylic plate was then removed from the tap water and dried for 10 minutes in a constant temperature dryer maintained at 50°C, with the wiped surface facing up, to obtain a treated sample.
[0163] In addition, as for an untreated (blank) acrylic plate that was not wiped with a sheet-like cleaning material impregnated with the liquid composition, the same operations as in the examples were carried out after drying for 10 minutes in a thermostatic dryer maintained at 50°C to obtain an untreated (blank) sample.
[0164] Blue colored water was prepared in a 100 ml beaker by dissolving 0.01 g of Blue No. 1 (powder) in 100 g of tap water.
[0165] Samples treated with the liquid composition-impregnated sheets of the Examples and Comparative Examples and an untreated sample (blank) were immersed in colored water and slowly pulled out, and the state of wetting with the water was observed and photographed.
[0166] The wet state of each item is shown in Table 1, and photos of each item at that time are shown in Table 2.
[0167] [Table 1]
[0168] [Table 2]
[0169] <Results and considerations regarding the stain resistance of acrylic sheets>
[0170] After wiping with the liquid composition-impregnated sheets of the Examples and Comparative Examples, the amount of carbon black adhering to the dried acrylic plate was almost the same for the Examples, Comparative Examples, and the untreated plate. The removal rate of the carbon black that washed off when water was subsequently sprayed on the plate was significantly higher for the Examples 1 and 2 plates than for the untreated plate and Comparative Examples 1 and 2 plates.
[0171] Next, the amount of carbon black adhering to the acrylic plate, which was wiped with the liquid composition-impregnated sheet of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried, was almost the same in the Examples, Comparative Examples, and the untreated plate. The removal rate of the carbon black that washed off when water was then sprayed on the acrylic plate was superiorly higher in the Examples 1 and 2 than in the untreated plate and the Comparative Examples 1 and 2. This is presumably due to the hydrophilizing effect of the xanthan gum, since the xanthan gum remained on the surface of the acrylic plate of the Examples even when immersed in water.
[0172] In Comparative Examples 1 and 2, when the plates were immersed in water for 10 minutes, the removal rate was lower than when they were not immersed. This is thought to be because the surfactant and xanthan gum remaining on the acrylic plate surface after wiping were dissolved and peeled off from the acrylic plate during immersion in water.
[0173] <Considerations on the stain-resistant properties of screen nets>
[0174] After wiping with the liquid composition-impregnated sheets of the Examples and Comparative Examples, the amount of carbon black adhering to the dried screen netting was almost the same for the Examples, Comparative Examples, and the untreated screen. The removal rate of the carbon black that washed off when water was then sprayed was significantly higher for the Examples 1 and 2 and Comparative Example 2 than for the untreated screen netting and Comparative Example 1. This is presumably due to the hydrophilizing effect of the xanthan gum remaining on the screen netting surface during the wiping treatment.
[0175] Next, the amount of carbon black adhering to the screen nets that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried also was almost the same for the Examples, Comparative Examples, and the untreated screen. The removal rate of the carbon black that washed off when water was then sprayed was significantly higher in the Examples 1 and 2 compared to the untreated screen and the Comparative Examples 1 and 2. This is presumably due to the hydrophilizing effect of the xanthan gum, since the xanthan gum remained on the surface of the screen net of the Examples even when immersed in water.
[0176] On the other hand, in Comparative Example 2, it is believed that the xanthan gum was unable to form an insoluble complex with the cationic base, and therefore dissolved and peeled off from the screen netting during immersion in water.
[0177] <Results and considerations regarding the antifouling properties of transparent glass plates>
[0178] The amount of carbon black adhering to the glass plate after wiping with the liquid composition-impregnated sheet of the Examples and Comparative Examples and drying was almost the same for the Examples, Comparative Examples, and the untreated glass plate. The removal rate of the carbon black that washed off when water was subsequently sprayed was significantly higher for the Examples 1 and 2 than for the untreated glass plate and the Comparative Examples 1 and 2.
[0179] Next, the amount of carbon black adhering to the glass plate, which was wiped with the liquid composition-impregnated sheet of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried, was almost the same in the Examples, Comparative Examples, and the untreated plate. The removal rate of the carbon black that washed off when water was then sprayed on the glass plate was superiorly higher in the Examples 1 and 2 than in the untreated plate and the Comparative Examples 1 and 2. This is presumably due to the hydrophilizing effect of the xanthan gum, since the xanthan gum remained on the glass plate surface even when the glass plate of the Examples was immersed in water.
[0180] In Comparative Examples 1 and 2, when the glass plate was immersed in water for 10 minutes, the removal rate was lower than when the glass plate was not immersed. This is thought to be because the surfactant and xanthan gum remaining on the glass plate surface after wiping were dissolved and peeled off from the glass plate during immersion in water.
[0181] <Results and discussion regarding water wettability of acrylic sheets (Table 1, Table 2)>
[0182] Regarding the water wettability of the acrylic plates that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried, Examples 1 and 2 showed uniform water wettability, whereas the untreated plates and Comparative Examples 1 and 2 showed water repellency. This is presumably because the xanthan gum of the acrylic plates of the Examples remained on the surface of the acrylic plates even when immersed in water, thereby exerting a hydrophilic effect. Table 2 shows photographs of the water wettability of the Examples, Comparative Examples, and untreated acrylic plates.
[0183] On the other hand, in Comparative Examples 1 and 2, it is believed that an insoluble complex could not be formed between xanthan gum and the cationic base, and therefore the surface of the acrylic plate could not be made hydrophilic.
[0184] <Results and considerations of antibacterial activity of acrylic sheets>
[0185] The antibacterial activity values of the acrylic plates wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples and then dried were superior to those of the untreated and Comparative Examples 2 in Examples 1 and 2 and Comparative Example 1 (values exceeding an antibacterial activity value of 2). In general, an antibacterial activity value of 2 or more is the standard for claiming an antibacterial effect. This is presumably due to the antibacterial effect of the cationic bases (benzalkonium chloride, dodecyltrimethylammonium chloride, polyhexamethylene biguanide) remaining on the surface of the acrylic plate during the wiping treatment.
[0186] Next, the antibacterial activity values of the acrylic sheets that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried showed significantly higher values (values exceeding antibacterial activity value 2) in Examples 1 and 2 than the untreated acrylic sheets and Comparative Examples 1 and 2. This is presumably due to the antibacterial effect of the cationic base, since the cationic base remained on the surface of the acrylic sheet of the Examples even when immersed in water.
[0187] On the other hand, in Comparative Example 1, it is believed that the cationic base was unable to form an insoluble complex with xanthan gum, and therefore the sample dissolved and peeled off from the acrylic plate during immersion in water.
[0188] <Results and considerations of antibacterial activity of screen net>
[0189] The antibacterial activity values of the screen nets wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples and then dried were superior to those of the untreated and Comparative Example 2 in Examples 1 and 2 and Comparative Example 1 (values exceeding antibacterial activity value 2). This is presumably due to the antibacterial effect of the cationic base remaining on the surface of the screen net during the wiping treatment.
[0190] Next, the antibacterial activity values of the screen nets that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried showed significantly higher values (antibacterial activity value exceeding 2) in Examples 1 and 2 than the untreated screen net and Comparative Examples 1 and 2. This is presumably due to the antibacterial effect of the cationic base, since the cationic base remained on the surface of the screen net in the Examples even when immersed in water.
[0191] On the other hand, in Comparative Example 1, it is believed that the cationic base was unable to form an insoluble complex with xanthan gum, and therefore the screen net dissolved and peeled off during immersion in water.
[0192] <Results and considerations of antibacterial activity value of transparent glass plate>
[0193] The antibacterial activity values of the glass plates wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples and then dried were superior to those of the untreated glass plate and Comparative Example 2 in the antibacterial activity values of Examples 1 and 2 and Comparative Example 1 (values exceeding antibacterial activity value 2). This is presumably due to the antibacterial effect of the cationic base remaining on the glass plate surface during the wiping treatment.
[0194] Next, the antibacterial activity values of glass plates that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried showed significantly higher values (values exceeding antibacterial activity value 2) in Examples 1 and 2 than the untreated glass plate and Comparative Examples 1 and 2. This is presumably due to the antibacterial effect of the cationic base, since the cationic base remained on the glass plate surface even when the glass plate of the Examples was immersed in water.
[0195] On the other hand, in Comparative Example 1, it is believed that the cationic base was unable to form an insoluble complex with xanthan gum, and therefore the sample dissolved and peeled off from the glass plate during immersion in water.
[0196] <Results and considerations of mold resistance test evaluation of acrylic sheets>
[0197] In the evaluation of the mold resistance test for acrylic sheets that were wiped with the liquid composition-impregnated sheets of the Examples and Comparative Examples, dried, and then immersed in tap water for 10 minutes and dried, Examples 1 and 2 showed a superior resistance evaluation rank compared to the untreated acrylic sheets and Comparative Examples 1 and 2. This is presumably due to the antifungal effect of the cationic base, since the cationic base remained on the surface of the acrylic sheet of the Examples even when immersed in water.
[0198] On the other hand, in Comparative Example 1, it is believed that the cationic base was unable to form an insoluble complex with xanthan gum, and therefore the sample dissolved and peeled off from the acrylic plate during immersion in water.
Claims
1. a) Water-soluble polymer having a carboxylic acid and / or a salt thereof: 0.05 to 5% by weight b) Antibacterial and / or bactericidal agents having a cationic group: 0.1 to 10% by weight c) Electrolyte: 0.1-15% by weight The present invention relates to a sheet-like cleaning article for imparting antifouling and / or antibacterial properties to a surface of an object, the sheet-like cleaning article being obtained by impregnating a liquid composition containing the above formula (I) into a sheet-like substrate, and the pH of the liquid composition in the sheet-like substrate is in the range of 3 to 12.
2. 2. The sheet-like cleaning article according to claim 1, which is used on a surface of an object and is capable of inhibiting adhesion of dirt to said surface after rinsing with water or after getting wet with rainwater or other water.
3. 2. The sheet-like cleaning article according to claim 1, which is applied to a surface of an object and can make the surface have antibacterial properties after being rinsed with water or after being wetted with rainwater or other water.
4. 2. The sheet-like cleaning article according to claim 1, which is capable of providing the surface with antibacterial and antifungal properties after being applied to the surface of an object and being rinsed with water or after being wetted with rainwater or other water.
5. The antibacterial agent and / or bactericide having a cationic group of the above b) is Alkylamine salt type cationic surfactants, alkenylamine salt type cationic surfactants, quaternary ammonium salt type cationic surfactants, pyridine ring salt-containing cationic surfactants, cationic polymers having a quaternary ammonium salt in the main chain or side chain, cationic polymers having a guanidine skeleton or biguanide skeleton in the main chain or side chain, cationic polymers having an amino group in the side chain, and guanidine skeleton or biguanide skeleton compounds other than polymers.
5. The sheet-like cleaning article according to claim 1, further comprising one or more antibacterial agents and / or bactericides selected from the group consisting of:
6. The antibacterial agent and / or bactericide having a cationic group of the above b) is 5. The sheet-like cleaning article according to claim 1, comprising a cationic surfactant having at least one linear or branched alkyl or alkenyl group having 6 to 20 carbon atoms, and / or a cationic polymer having a guanidine skeleton or a biguanide skeleton.
7. The antibacterial agent and / or bactericide having a cationic group of the above b) is 5. The sheet-like cleaning article according to claim 1, comprising one or more selected from the group consisting of polyhexamethylene guanidine or a salt thereof, polyaminopropyl biguanide or a salt thereof, polyhexamethylene biguanide or a salt thereof, and chlorhexidine or a salt thereof.
8. The antibacterial agent and / or bactericide having a cationic group of the above b) is 8. The sheet-form cleaning article according to claim 7, further comprising a quaternary ammonium salt type cationic surfactant.
9. 5. The sheet-like cleaning article according to any one of claims 1 to 4, wherein the water-soluble polymer having a carboxylic acid and / or a salt thereof is xanthan gum, pectin and / or a salt thereof, gellan gum and / or a salt thereof, diutan gum, welan gum, gum arabic and / or a salt thereof, alginic acid and / or a salt thereof, hyaluronic acid and / or a salt thereof, tragacanth gum and / or a salt thereof, succinoglycan and / or a salt thereof, carboxymethylcellulose and / or a salt thereof, carboxyethylcellulose and / or a salt thereof, carboxyvinyl polymer and / or a salt thereof, or polyacrylic acid and / or a salt thereof.
10. 5. The sheet-like cleaning article according to claim 1, wherein the water-soluble polymer having a carboxylic acid and / or a salt thereof is xanthan gum.
11. 5. The sheet-like cleaning article according to claim 1, wherein the electrolyte c) is one or more electrolytes selected from the group consisting of inorganic acids and / or salts thereof, monovalent organic acids and / or salts thereof, polycarboxylic acids and / or salts thereof having metal chelating ability, polyphosphonic acids and / or salts thereof having metal chelating ability, and polyphosphoric acids and / or salts thereof having metal chelating ability.
12. The electrolyte of c) is Hydrochloric, sulfuric, carbonic, phosphoric, and silicic acids and their respective alkali metal, alkaline earth metal, and zinc salts; Formic acid, acetic acid, lactic acid, propionic acid, and benzoic acid, and their respective alkali metal, alkaline earth metal, and zinc salts; malonic acid, succinic acid, glutaric acid, gluconic acid, malic acid, citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, diethylenetriaminepentaacetic acid, hydroxyethylethylenetriacetic acid, and hydroxyethyliminodiacetic acid, and their respective salts; Polyphosphonic acid and / or its salts; and Polyphosphoric acid and / or its salts 12. The sheet-like cleaning article according to claim 11, wherein the electrolyte is one or more selected from the following:
13. 5. The sheet-like cleaning article according to claim 1, which has a viscosity in the range of 20 to 500 mPa·s under measurement conditions described in the specification.
14. 5. The sheet-like cleaning article according to claim 1, which contains 0.5 to 10% by weight of an alkyl glucoside.
15. 5. The sheet-like cleaning article according to claim 1, which contains 2 to 30% by weight of glycol and / or glycol ether.
16. 16. The sheet-like cleaning article according to claim 15, wherein said glycol is hexylene glycol and said glycol ether is diethylene glycol monobutyl ether and / or propylene glycol monomethyl ether.
17. The sheet-like cleaning article according to any one of claims 1 to 4, wherein the sheet-like substrate is selected from the group consisting of paper, nonwoven fabric, woven fabric, a composite substrate of paper and nonwoven fabric, a composite substrate of nonwoven fabric and woven fabric, a composite substrate of paper and film, a composite substrate of nonwoven fabric and film, a composite substrate of woven fabric and film, and a composite substrate of paper, nonwoven fabric, and film.
18. 5. The sheet-like cleaning article according to claim 1, wherein the weight ratio of the liquid composition to be impregnated to the sheet-like substrate is 1.5 to 10 times.
19. 5. The sheet-like cleaning article according to claim 1, wherein the sheet-like substrate contains cellulosic fibers, and the cellulosic fibers are contained in the sheet-like substrate in an amount of less than 40% by weight.
20. 5. The sheet-like cleaning article according to claim 1, wherein the surface of the target object is a hard surface, a soft surface, a woven surface, a non-woven surface, or a film surface made of glass, pottery, enamel, wood, bamboo, synthetic resin, ceramics, stainless steel, or aluminum.
21. 21. The sheet-like cleaning article according to claim 20, wherein the surface of the target object is a glass window, a screen door, a blind, a shutter, a door, a curtain, a vehicle cover, an outer wall, an inner wall, an umbrella, a spectacle lens, or sunglasses.
Citation Information
Patent Citations
Wet tissue
JP2002233471A
Deodorizing antifoulant
JP2002336337A
Wet sheet
JP2021028333A
Liquid stain-resistant cleaner composition and method for antifouling treatment
JP2022089322A
Acidic cleaning and disinfecting compositions
WO2022040332A1